Transferrin polymorphism and its correlation with lactation length and dry period in Tarai buffalo and Sahiwal cattle - Jaswant Singh; RB Prasad; Sunil Kumar (Journal of Livestock Biodiversity, 2025)
In the present study a total of 50 Tarai buffalo and 30 Sahiwal cattle were typed for transferrin. Two BC CC B C transferrin phenotypes were found viz. T and T in Tarai buffalo with gene frequency of T and T as f f f f 0.14 and 0.86, respectively.